Littlewood–Paley theorem on spaces Lp(t)(ℝⁿ) - Kopaliani, T.S. (Український математичний журнал, 2008)
We point out that if the Hardy–Littlewood maximal operator is bounded on the space Lp(t)(ℝ), 1 < a ≤ p(t) ≤ b < ∞, t ∈ ℝ, then the well-known characterization of the spaces Lp(ℝ), 1 < p < ∞, by the Littlewood–Paley theory extends to the space L p(t)(ℝ). We show that, for n > 1 , the Littlewood–Paley operator is bounded on Lp(t) (ℝⁿ), 1 < a ≤ p(t) ≤ b < ∞, t ∈ ℝⁿ, if and only if p(t) = const. Встановлено, що коли максимальний оператор Харді - Літтлвуда обмежений на просторі Lp(t)(Rⁿ), 1<a ≤ p(t) ≤ b < ∞,t∈R, добре відома характеризація просторів Lp(t)(Rⁿ),1<p<∞ теорією Літтлвуда - Пелі поширюється на простір Lp(t)(Rⁿ). Показано, що у випадку n>1, оператор Літтлвуда - Пелі обмежений на Lp(t)(Rⁿ),1 < a ≤ p(t) ≤ b<∞,t ∈ R, тоді і тільки тоді, коли p(t)= const.